2018
DOI: 10.1016/j.jocn.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

MRI measurements of the normal pediatric optic nerve pathway

Abstract: The purpose of this work is to establish a reference scale of optic nerve pathway measurements in pediatric patients according to age using MRI. Optic nerve pathway measurements were retrospectively analyzed using an orbits equivalent sequence on brain MRI scans of 137 pediatric patients (72 male, 65 female, average age = 7.7 years, standard deviation  = 5.3). The examinations were performed on a 1.5-T or 3-T Siemens MR system using routine imaging protocols. Measurements include diameters of the orbital optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
4
10
0
Order By: Relevance
“…3 Also this study agreement the study done by Maresky et al found that a strong positive correlation was established between age and mean diameter of OON and the measurement of OON increase with age. 2 The diameter of ON slightly more in females than the males with no significant difference, this result agreement with study done by Al-Haddad et al whom found that optic nerve diameter not differ in both sexes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3 Also this study agreement the study done by Maresky et al found that a strong positive correlation was established between age and mean diameter of OON and the measurement of OON increase with age. 2 The diameter of ON slightly more in females than the males with no significant difference, this result agreement with study done by Al-Haddad et al whom found that optic nerve diameter not differ in both sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Various pathologies affecting the ONs, isolated or associated with other intracranial abnormalities, measuring the optic pathway is important and aid in the diagnosis of many pathologies, congenital malformations, and acquired diseases are affect the ON and associated structures, increased in ON diameter is seen in increased idiopathic intracranial hypertension, small optic pathways can be indicative of several disorders, with the most severe of them being septo-optic dysplasia and ON hypoplasia, a large optic pathway may be indicative of glioma, meningioma, lymphoma, or hemorrhage. 1,2 MRI an outstanding depiction of the complicated anatomy of the ON because of its determinizations of tissue contrast without using ionizing radiation, it was a higher delineation of the whole visible pathway and correct assessment of related intracranial pathologies. 3 Many studies found that there was an importance of measuring the ONs to make a standard scale for evaluation of ON abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Volumetry has been widely validated in neurologic and orbital studies and is reproducible. 1,4 Finally, we agree with the authors that there is a need to establish a standardized method for the measurement of the optic nerve on MR imaging, but we believe that volumetric measurements should be made including the entire volume of the optic nerve starting from the papilla and ending at the point of convergence of the extraocular muscles at the tendinous ring of the orbital apex, 1 or ending at the chiasma, to provide accurate and reproducible measurements.…”
supporting
confidence: 75%
“…Optic nerve imaging protocols usually include multi-slice T1 and T2-weighted scans in both axial and coronal orientations, as well as post-contrast scans [2,3]. Partial volume effects in two-dimensional sequences, however, often compromise accurate depiction of the optic nerves along their full extent.…”
Section: Introductionmentioning
confidence: 99%